The trade-off unemployment rate/external deficit : assessing the economic adjustment program of the troika (European Commission, ECB and IMF) for Portugal using an input-output approach - Amaral, João Ferreira do (2015)
This article presents an evaluation of the economic adjustment program negotiated between the Portuguese government and the Troika (European Commission, ECB and IMF) in May 2011, with an assessment different from the usual exercises. Instead of an ex-post comparison between the actual results and the proposed targets, an ex-ante assessment of the forecast errors is made. It is shown that these errors could be avoided if the productive (input-output) structure of the economy and the unemployment/external deficit trade-off were taken into account. The main conclusion of this assessment, a large under-estimation of the unemployment rate of about 4 percentage points, illustrates the technical incompetence of this adjustment program and the huge economic and social costs it unnecessarily caused. The methodology used can easily be replicated in assessing other similar programs, such those applied in Greece, Ireland and Cyprus.